Chitosan/Xanthan Gum Based Hydrogels as Potential Carrier for an Antiviral Drug: Fabrication, Characterization, and Safety Evaluation - Malik, Nadia Shamshad; Ahmad, Mahmood; Minhas, Muhamad Usman; Tulain, Ruqia; Barkat, Kashif; Khalid, Ikrima; Khalid, Qandeel (Frontiers in Chemistry, 2020)
This study investigated the use of pure polymer chitosan (CS), xanthan gum (XG), monomer 2-acrylamido-2-methylpropane sulfonic acid (AMPS) and initiator potassium persulfate (KPS) as drug carrier system crosslinked through N′ N′-methylene bis-acrylamide (MBA) for controlled drug delivery of acyclovir (ACV). ACV is highly effective and selective antiviral drugs used for prophylaxis and treatment against herpes simplex viruses (HSV) infections. Present oral marketed formulations are associated with number of side effects and shortcomings which hampered its clinical effectiveness. Hydrogels (FCX1-FCX9) composed of CS, XG, AMPS, MBA, and KPS were prepared by free radical polymerization technique and characterized through FTIR, PXRD, thermal analysis and SEM. Swelling dynamics and drug release behavior was also investigated. FTIR studies confirmed that ACV was successfully encapsulated into hydrogel polymeric network. SEM revealed porous structure whereas thermal analysis showed enhanced thermal stability of polymeric network. PXRD indicated amorphous dispersion of ACV during preparation process. Swelling dynamics and ACV release behavior from developed hydrogels was dependent on pH of the medium and concentration of pure reactants used. Korsmeyer-Peppas model was best fit to regression coefficient. The present work demonstrated a potential for developing a pH sensitive hydrogel for an antiviral drug ACV by using pure polymers CS, XG, and monomer AMPS.